Decadal variability of phytoplankton seasonal cycles in the Northern Hemisphere, as related to mixed-layer depth changes - Martinez, E.; Antoine, David; D'Ortenzio, F.; de Boyer Montégut, C. (AGU, 2010)
Using two decades of satellite ocean color observations (including CZCS and SeaWiFS data) spatial and temporal covariability between ocean chlorophyll (Chl) and Sea Surface Temperature (SST) have been recently investigated to highlight the long-term variability. A Chl-SST inverse relationship was frequently observed, and decadal changes in Chl essentially result from basin-scale low-frequency natural oscillations of the physical environment. The objective is now to investigate changes in seasonal cycles that may have occurred besides the long-term changes. The study concentrates on the northern hemisphere where the CZCS scattered distribution has a sufficient coverage in space and time to investigate the seasonal cycles. Mixed-layer depths (MLD) are used to investigate the role of the oceanic stratification in the observed Chl changes. In the northern Atlantic and Pacific as the maximum MLD in winter is deeper over 1998-2002 than 1979-1983, the spring bloom intensity increases. Inversely, the fall bloom weakens over the SeaWiFS era as ML started to deepen one month later. In the western Arabian Sea, the productivity increases during the Southwest Monsoon as MLD maximum is deeper.